(untitled) - Simona Kelčíková; Marcela Pydová; Nora Malinovská (University of Ostrava, 2020)
Aim: The aim of the study was to survey adolescent sexual behavior, use of contraceptives, and sexually transmitted infections, and, in addition, to see how these factors correlated with selected individual characteristics of the respondents (e.g., age, gender). Design: A quantitative cross-sectional study. Methods: An exploratory method, using a specially designed questionnaire, was selected. The research sample consisted of 381 adolescents with an average age of 17.75 years (± 1.28). Data were analyzed using descriptive statistics and the Chi-squared (χ2) test (p < 0.05). Results: More than half of adolescents (61.35%; 2.49 ± 1.91) have had sexual intercourse. We found a variety of reasons for differences in the use of contraceptive methods. The most commonly used contraceptive methods during sexual intercourse were male condoms (50.13%), and hormonal pills (16.80%). However, most respondents (86.61%) reported they had not used condoms during their last sexual intercourse. Only 12.86% of respondents considered their sexual behavior safe. Statistically significant differences were found in adolescent sexual behavior relating to contraceptive use in terms of gender and age (p < 0.05). Male adolescents were more likely to use condoms during sexual intercourse, and to use contraceptive methods to prevent sexually transmitted infections. Conclusion: The study revealed that the level of adolescent sexual behavior deserves more attention. Evidence of significant differences should serve as an argument for efforts to increase awareness and education on issues related to sexual health, with an emphasis on the risk of sexually transmitted infections.